Visions and practices of education as transformative tools - Rosa Bruno-Jofré; Diana Gonçalves Vidal (Cadernos de História da Educação, 2023)
The six articles in this dossier were prepared for a cancelled symposium that was to take place in Salvador, Bahia, in July 2022. The planned symposium was part of a Social Sciences and Humanities Research Council of Canada (SSHRC) Connection Grant , and was to gather members of the Theory and History of Education International Research Group (THEIRG), housed at the Faculty of Education, Queen’s University (https://educ.queensu.ca/their), along with members of the History of Education Research Group (NIEPHE) (https://sites.usp.br/niephe/) and the Thematic Project Education in Borders (https://sites.usp.br/educacaoemfronteiras/) of the University of São Paulo. The papers have in common the analysis of visions of education and educational aims in relation to social conceptions of change, along with a theological, philosophical, or socio-political ethical foundation. The authors do not neglect the agency of the individual as either an individual or a collective self – neither the contextual nuances nor the unexpected implications of the educational process.